Effect of Marigold Extract in Controlling Cowpea Aphid, Aphis craccivora Koch (Homoptera: Aphididae) - Matintarangson, Nathapong; Wattanuruk, Duangduan (Journal of Food Health and Bioenvironmental Science, 2018)
The objective of this study was tested as the repellent, insecticidal and anti-feedant activity of ethanol extracts from marigold extract, Tagetes erecta L. on cowpea aphid, Aphis craccivora Koch. The leaf dipping method at various concentrations of marigold extract 0, 0.5, 1, 2, 4 and 8% (w/v) were applied. The results found that the repellent, insecticidal and anti-feedant activity of marigold extract on cowpea aphid were significantly effective high (p<0.05). The concentration at 8% of marigold extract, the percent repellent was the highest value with 60% at 24 hr and 100% at 48 hr. The anti-feedant activity, the number of probing was high when the concentration was high. The concentration at 8% of marigold extract, the number of probing was the highest with 8.20 + 0.74 at 15 min when compared with the control 1.40 + 0.48. Time of penetration was low when the concentration was high. The concentration at 8% of marigold extract, time of penetration was the least with 0.17 + 0.03 min when compared with the control 8.74 + 1.03 min. The percent mortality was the highest 100% and the LC50 at 24 and 48 hr value with 2.38 and 1.64, respectively. Therefore, the use of marigold extract can be protect the cowpea aphid as the repellent, insecticidal and anti-feedant activity and reduce the use synthetic chemicals, save the human health and environment.